2010
DOI: 10.1021/cg100429b
|View full text |Cite
|
Sign up to set email alerts
|

The Czochralski Growth of (Lu1−xGdx)2SiO5:Dy Single Crystals: Structural, Optical, and Dielectric Characterization

Abstract: The Czochralski growth of Dy 3þ -doped (Lu 1-x Gd x ) 2 SiO 5 solid solution single crystals with different mixtures of Lu 2 SiO 5 and Gd 2 SiO 5 oxides (x = 0, 0.2, 0.4, 0.6, 0.8, and 1) is reported. It was found that the (Lu 1-x Gd x ) 2 SiO 5 crystals retain structural, physical, and optical properties of Lu 2 SiO 5 even for x = 0.8. Optical investigation of Dy:(Lu 1-x Gd x ) 2 SiO 5 revealed that the structural disorder of the host brings about a strong inhomogeneous broadening of Dy 3þ spectral bands whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 16 publications
4
21
0
Order By: Relevance
“…Recently O. Sidletskiy et al [25] reported a light output by ∼ 70% with respect to Ce:LSO crystals, energy resolution of 6.9 -7.3% at 662 keV ( 137 Cs), slow decay component of only several percents, and lower afterglow level by choosing an optimal Lu content at 30 -60 at.% with the C2/c symmetry and Ce concentration of no more than 0.6 at.%. Besides Ce doping, the (Lu x Gd 1−x ) 2 SiO 5 crystal has also been investigated with Dy 3+ doping [26] and Er 3+ , Yb 3+ codoping [27]. It presented a substantial broadening of dysprosium absorption and emission lines in (Lu x Gd 1−x ) 2 SiO 5 , confirming a structural disorder produced by the substitution of much large Gd 3+ ions in the ordered lutetium oxyorthosilicate (LSO) C2/c structure [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently O. Sidletskiy et al [25] reported a light output by ∼ 70% with respect to Ce:LSO crystals, energy resolution of 6.9 -7.3% at 662 keV ( 137 Cs), slow decay component of only several percents, and lower afterglow level by choosing an optimal Lu content at 30 -60 at.% with the C2/c symmetry and Ce concentration of no more than 0.6 at.%. Besides Ce doping, the (Lu x Gd 1−x ) 2 SiO 5 crystal has also been investigated with Dy 3+ doping [26] and Er 3+ , Yb 3+ codoping [27]. It presented a substantial broadening of dysprosium absorption and emission lines in (Lu x Gd 1−x ) 2 SiO 5 , confirming a structural disorder produced by the substitution of much large Gd 3+ ions in the ordered lutetium oxyorthosilicate (LSO) C2/c structure [26].…”
Section: Introductionmentioning
confidence: 99%
“…Besides Ce doping, the (Lu x Gd 1−x ) 2 SiO 5 crystal has also been investigated with Dy 3+ doping [26] and Er 3+ , Yb 3+ codoping [27]. It presented a substantial broadening of dysprosium absorption and emission lines in (Lu x Gd 1−x ) 2 SiO 5 , confirming a structural disorder produced by the substitution of much large Gd 3+ ions in the ordered lutetium oxyorthosilicate (LSO) C2/c structure [26]. L. Han et al [27] have studied the upconversion (UC) and near infrared (NIR) emission properties of Er 3+ , Yb 3+ :LGSO crystal and reported an intense UC emission with standardized efficiencies as high as 0.83×10 −3 (green) and 0.93×10 −3 (red), respectively, and an efficient NIR emission at 1543 nm with σ em = 0.994×10 −20 cm 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Effective laser action at around 1µm has been reported for LSO doped with ytterbium ions [16]. Furthermore, LSO and GSO doped with Dy 3+ and Sm 3+ owing to an intense luminescence in the blue and yellow spectral range can be promising systems for applications as white light emitters [1,17].…”
mentioning
confidence: 99%
“…The crystals in whose formulae RE stands for rare earth ions from La to Tb crystallize in P2 1 /c space group, while those in whose formulae RE stands for ions from Dy to Lu crystallize in C2/c space group [1,17]. Many ways of realization of isomorphic lattices with monoclinic space group symmetry open the possibility of obtaining doped oxyorthosilicate crystals by substitution of one rare earth element by another [18].…”
mentioning
confidence: 99%
See 1 more Smart Citation